Congenital arch vessel anomalies in CHARGE syndrome: A frequent feature with risk for co-morbidity. (September 2016) - Corsten-Janssen, Nicole; van Ravenswaaij-Arts, Conny M.A.; Kapusta, Livia
Abstract: Background: CHARGE syndrome is a complex multiple congenital malformation disorder with variable expression that is caused by mutations in the CHD7 gene. Variable heart defects occur in 74% of patients with a CHD7 mutation, with an overrepresentation of atrioventricular septal defects and conotruncal defects — including arch vessel anomalies. Methods and results: We report an index patient with an arch vessel anomaly underlying serious feeding problems that resolved after arch vessel surgery. This led us to examine the incidence of arch vessel anomalies in our previously studied cohort of 299 patients with a CHD7 mutation. Forty-two patients (14%) had an aortic arch anomaly, mostly aberrant subclavian artery or right aortic arch, which usually occurred in combination with other congenital heart defects (81%). The majority of these patients also had feeding problems that may be linked to their arch anomaly, but insufficient information was available to exclude other causes. Conclusions: Arch vessel anomalies occur in a significant proportion of patients with a CHD7 mutation, and these anomalies may cause morbidity due to compression of the esophagus or trachea. Since symptoms of vascular compression can mimic those caused by other abnormalities in CHARGE syndrome, it is important to be aware of arch vessel anomalies in this complex patient category. Whether a solitary arch vessel anomaly is an indicator for CHARGE syndrome still needs to be studied, but doctors should look out for other CHARGE syndrome features in patients with arch vessel anomalies.